Evaluation of Mewari, a native chicken breed vis-à-vis Pratapdhan, an improved chicken variety under an intensive system of rearing - JAREDA, PRATIBHA; MISHRA, SIDDHARTHA; RAJKUMAR, ULLENGALA (The Indian Journal of Animal Sciences, 2022)
Mewari is an indigenous chicken breed and Pratapdhan is a dual purpose chicken variety developed using Mewari, coloured broiler and Rhode Island Red. Pratapdhan birds were well accepted by the farmers of Rajasthan and adjoining areas. The study was undertaken for comparative evaluation of Mewari and Pratapdhan chicken under intensive system. The data were analyzed using factorial design with genotype, sex and generation (2 × 2 × 3) as main effects. The body weights differed significantly at all ages with significant higher weights in Pratapdhan as compared to Mewari chicken. Sex had significant effect on body weights at all ages except at 2nd week. Males had significantly higher body weights across the genotypes and generations. The interaction effects were significant between the genotypes, sex and generations, except at 2nd week of age. The body weights showed an increasing trend over the generations with few exceptions. ASM and egg weights significantly varied between the genotypes and across the generations with significant interaction effects. The average annual egg production and egg weight (72 weeks) in Mewari and Pratapdhan chicken were 92.02±0.52 and 158.25±1.20 and 46.85±0.22 and 55.74±0.28, respectively. The fertility per cent was 80.39±1.45 and 83.28±0.64 in Mewari and Pratapdhan, respectively. The results suggest that Pratapdhan could be one of the potential improved germplasm for backyard poultry production.